Meeting Africa's employment challenge in a changing world - Tilman Altenburg; Brahima Coulibaly (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Around 2031, Africa's working-age population will pass the 1-billion threshold. This growing workforce will require decent productive employment. So far, Africa's economies have largely failed to create stable and well-paid jobs. For any one person working in the formal private sector, 10 work in the informal economy. Failure to generate sufficient formal-sector jobs for young people will increase migration and global security challenges. Creating decent jobs at the scale required is inconceivable without a structural transformation that enables workers to move from low-productivity agriculture and informal trades to modern manufacturing or service sectors. Such a transformation took place in some East Asian countries, but no comparable dynamic has so far been observed anywhere in Africa. What's more, the region has already started to deindustrialise at a stage when industry has not yet really taken off. What, then, are the prospects for Africa's economic future? Where should the millions of decent jobs the region urgently needs come from? We suggest exploring this not by extrapolating past trends, but by analysing how certain – potentially disruptive – global trends impact on African economies: Natural resources are being depleted globally while the world population increases, becomes more affluent and demands higher-value food. Also, the global bioeconomy is likely to boost demand for fuel substitutes. This creates opportunities for countries with underutilised land resources. Urbanisation and the expansion of African middle classes will boost and diversify demand, creating opportunities for local consumer industries. Trends towards sustainable smart cities also hold promises for African entrepreneurs in transport, electronics, the construction industry and other sectors. New digital technologies improve connectivity. Some digital innovations enable African producers to tap into hitherto inaccessible markets, whereas others may lead to automation and global market concentration at the expense of African producers. China's rapidly increasing wages may lead to the relocation of labour-intensive industries to African countries with low unit labour costs – unless China uses auto¬mation to keep them at home. The imperative of reducing the world economy's material footprint may create new opportunities, such as in low-input agriculture or electrification based on low-cost renewable energy. At the same time, it creates the risk of enormous capital losses in high-carbon and other unsustainable technologies. We do not know exactly how these trends will play out for individual African countries. Yet some trends will be game-changing. Hence, we recommend systematic efforts to explore them, with the aim of identifying competitive opportunities and taking strategic action early on. We identify some opportunities in manu¬facturing and services that we expect to become important (while recognising big differences across the region). We also suggest complementary investments in productivity and employment for the large proportion of the workforce not easily and immediately employable in competitive industries.
Keywords: 330; Strukturwandel; wirtschaftliche Entwicklung und Beschäftigung